Entrance to the Mandapa of the Kumbheshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the main mandapa (pillared hall) entrance to the Kumbheshwar Mahadev Temple. The outer walls of the mandapa have undergone restorations.